Eficácia in vitro e in vivo da cefoperazona sódica, gentamicina e ciprofloxacino no tratamento intramamário da mastite clínica bovina - Maiolino, Sérgio Ricardo [UNESP] (2013)
This study compared the in vitro and in vivo efficacy of sodium cefoperazone, gentamicin and ciprofloxacin for the intramammary treatment of clinical mastitis in cows. Thirty cows suffering from non-systemic, clinical mastitis were divided into three groups of ten animals each. One of the above mentioned antibiotics was used in each group for conventional (i.e., three administrations of the drug, each 12 hours) and extended (i.e., six administrations of the drug, each 12 hours) treatments of mastitis. The most common microorganisms isolated from cows were Staphylococcus aureus, Staphylococus spp., Streptocccus spp. and enterobactéria. The efficacy of clinical cure of the conventional treatment was 50%, 70% and 50% for the groups treated with sodium cefoperazone, gentamicin and ciprofloxacin, respectively. Regarding the extended treatment, efficacy was 90%, 100% and 80%, for sodium cefoperazone, gentamicin and ciprofloxacin, respectively. Efficacy of bacteriological cure was 100% for sodium cefoperazone, and 90% for both gentamicin and ciprofloxacin using the conventional treatment. By using the extended treatment, efficacy of bacteriological cure was 100% for gentamicin and 90% for both cefoperazone and ciprofloxacin. Statistical differences (p>0.01) were not found in clinical or in bacteriological cure into the same group or among groups. Similarly, statistical differences between the conventional and extended treatments were not found. The results from this study reinforce the importance of performing microbiological culture of milk and in vitro antimicrobial sensitivity tests for supporting the intramammary treatment of clinical mastitis in cows. The clinical and bacteriological efficacy of sodium cefoperazone, gentamicin and ciprofloxacin in lactating cows was also observed in both conventional and extended treatments provided the use of sensitivity tests in vitro. Extended treatments should be used in selected cases of bovine mastitis